Construction and Statistical Analysis of the Multidimensional Inventory of Romantic Jealousy: Preliminary Study - Mota Palma, Jaqueline; González-Arratia López-Fuentes, Norma Ivonne; Valdez Medina, José Luis; González Escobar, Sergio; Hernández Vergara, Gabriela (Actualidades en Psicología, 2016)
Aiming to construct and validate a test to measure jealousy, the Multidimensional Inventory of Romantic Jealousy (MIRJ) was developed from three axes: 1) the notion of jealousy, 2) the situations that generate it and 3) cognitive, affective and behavioral responses involved. The MIRJ consists of five Likert scales with five response options each. The inventory was validated by expert judgment on the content validity and exploratory factor analysis to construct the validity of each scale, showing higher reliability coefficients (α > .85). MIRJ has a fairly clear structure with independent dimensions that measure with reasonable accuracy the three axes. In Conclusion, romantic jealousy is a multidimensional construct with affective, cognitive and behavioral responses, triggered from a situation that represents the possible loss of a partner.